2019
DOI: 10.3892/etm.2019.7188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy and nephrotoxicity during vancomycin therapy: A retrospective study in China

Abstract: The aim of the present study was to investigate the predictive value of vancomycin serum concentrations regarding its efficacy and nephrotoxicity in a Chinese population and to determine a relatively safe optimal target concentration during vancomycin therapy. A total of 65 patients that received vancomycin between March 2013 and March 2018 at Shanghai 10th People's Hospital (Shanghai, China) were enrolled and their vancomycin trough and peak concentrations were monitored. Factor analysis was performed in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…111,112 An AUC 0–24 /MIC ratio of ≥400 is recommended for improved clinical response against S. aureus infection, 29,94,103,107,109,112,150–152 whereas higher exposures are probably required when treating critically ill patients with septic shock. 29 Prolonged (≥7 days) and high vancomycin exposure, especially C min concentrations of >15 mg/L 96,98,102,153,154 or AUC 0–24 exposures of >600, 95–97 is commonly associated with nephrotoxicity. Alternative indices, including AUC 0–48 142 and AUC 24–48 , 28,108,155 have also been suggested to monitor the efficacy and toxicity of vancomycin.…”
Section: Glycopeptidesmentioning
confidence: 99%
“…critically ill patients with septic shock. 29 Prolonged ($7 days) and high vancomycin exposure, especially C min concentrations of .15 mg/L 96,98,102,153,154 or AUC 0-24 exposures of .600, [95][96][97] is commonly associated with nephrotoxicity. Alternative indices, including AUC 0-48 142 and AUC 24-48 , 28,108,155 have also been suggested to monitor the efficacy and toxicity of vancomycin.…”
Section: Vancomycinmentioning
confidence: 99%
“…Therapeutic drug monitoring of aminoglycosides is essential because of their potential ototoxicity and nephrotoxicity [5]. Vancomycin is an antibiotic also used for the treatment of serious infections which can cause serious life-threatening side effects [6]. Theophylline is a bronchodilator used to treat asthma symptoms for which overdose can occur rapidly [7].…”
Section: Mots Clés: Suivi Thérapeutique Pharmacologique Petinia (Particle Enhanced Turbidimetric Inhibition Immunoassay) Alinity Plasmamentioning
confidence: 99%